What's new in Ionic 3 framework : everything you need to know in 15 minutes (O'Reilly, 2017)
"Take a detailed look at Ionic 3's new features and capabilities in this video by Ionic expert Chris Griffith. Designed for the beginning- to intermediate-level developer, the course explores improvements to the Ionic command-line interface (CLI), investigates the new lazy-loading system, and previews what's in store for Ionic Creator."--Resource description page